Academic adaptation amid internationalisation: the challenges for local, mainland Chinese, and international students at Hong Kong's universities. Issue 4 (2nd October 2017) - Yu, Baohua; Wright, Ewan
Abstract : Internationalisation has been actively pursued by Hong Kong's universities. Recent years have witnessed quantitative growth in non-local students. To ensure a qualitative success of internationalisation, it is crucial that universities cater for students with diverse academic backgrounds. This research explored challenges to academic adaptation. Focus group interviews were conducted with 124 local, mainland Chinese and international students at four Hong Kong universities. Findings revealed variation in academic adaptation challenges. First, adaptation to an English-medium-of-instruction was a concern for local and mainland Chinese students, while international students noted that limited English proficiency among other students undermined classroom discussions and led to tensions in group projects. Second, local students faced challenges in adapting to a wider range of assessment modes and academic writing, while mainland Chinese and international students reported how teacher-student relations and teaching approaches differed from prior educational experiences. Implications for the delivery of higher education amid internationalisation are discussed.